Resource Allocation Optimization for Orthogonal Frequency Division Multiplexing Access using Modified Utility Function (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
In this paper, we propose an optimal method for resource allocation in OFDMA (Orthogonal Frequency Division Multiplexing Access) system. The utility function is used to balance the efficiency and fairness of wireless resource allocation. We analyze the mathematical property of resource allocation by modified utility function. We develop optimal algorithm for dynamic subcarrier assignment and adaptive power allocation based on modified utility function, and demonstrate the convergence properties of optimization. Simulation results show that the proposed method provides the effective tradeoff between fairness and efficiency in radio resource allocation.